The Relationship Between Workload and Work-Life Balance and Job Satisfaction of Employees at PT. X Medan - Effendi, Khairunnisa; Indriani, Fatma (LPPM Universitas Mohammad Husni Thamrin, 2025)
In the era of globalization, increasingly fierce business competition requires companies to have competent and high-performing human resources. Job satisfaction is a crucial aspect in the workplace that influences productivity and employee well-being, where excessive workload and imbalance in work-life balance can impact job satisfaction. This study aims to analyze the relationship between workload and work-life balance on employee job satisfaction at PT.X Medan. This study used a quantitative approach with a cross-sectional design. The sampling technique used purposive sampling of 50 employees from the Engineering and Processing Division. The data were analyzed using Pearson's correlation test Product Moment test. The results of the study indicate a very strong and significant negative relationship between workload and job satisfaction (r = -0.977), meaning that as workload increases, job satisfaction tends to decrease. Conversely, there is a very strong and significant positive correlation between work-life balance and job satisfaction (r = 0.958), indicating that the better the work-life balance, the higher the job satisfaction. These results confirm that high workload and poor work-life balance are associated with a decrease in employee job satisfaction. Therefore, evaluating and redistributing workload more proportionally, as well as implementing policies that support work-life balance for employees, are important for improving overall job satisfaction.